Educational interventions for cervical cancer prevention: a scoping review - Josiane Montanho Mariño; Lailah Maria Pinto Nunes; Yasmin Cardoso Metwaly Mohamed Ali; Leonardo do Carmo Tonhi; Marina de Góes Salvetti (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify, map and describe characteristics of educational interventions for cervical cancer prevention in adult women. Methods: a scoping review conducted on eleven databases and the gray literature, including studies that described educational interventions aimed at preventing cervical cancer in adult women. Results: thirty-three articles with 151,457 participants were analyzed. The most used educational strategies were participatory discussions and educational leaflets. Most of the interventions took place in a single session, ranging from 40 to 60 minutes. The most used theoretical model in interventions to improve women's compliance with Pap smear was the Health Belief Model. Conclusions: group discussions, lectures and educational brochures can increase knowledge and reduce barriers to cervical cancer prevention. Theory-based and culturally sensitive interventions can have a positive impact on women's health.